I need help solving

Tutors, sign in to answer this question.

You are on right track

2(x-3) + 1 = 3x -4

2x - 6 +1 = 3x - 4

2x -5 = 3x -4

subtract 2x from both sides

2x - 2x -5 = 3x - 2x -4

-5 = x -4

add + 5 on both sides

- 5 + 5 = x -4 + 5

0 = x + 1

add -1 on both sides

-1 = x +1 -1

-1 = x

:)

Hi Lashae;

2(x-3)+1=3x=4

I assume this is...

2(x-3)+1=3x+4

IF I AM MISTAKEN, PLEASE LET ME KNOW.

Let's distribute the 2...

2x-6+1=3x+4

2x-5=3x+4

Let's subtract 2x from both sides...

-2x+2x-5=-2x+3x+4

-5=x+4

Let's subtract 4 from both sides...

-4-5=x+4-4

Let's check our work...

2(x-3)+1=3x+4

2(-9-3)+1=[(3)(-9)]+4

2(-12)+1=(-27)+4

-24+1=-23

-23=-23

Jusyt multiply it out, combine similar terms, and solve.

2(x-3)+1=3x-4 (assume typo, it is minus 4, not equals 4?)

2x-6+1=3x-4

Subtract 2x from both sides ... 5=x-4 ... x=9

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.

## Comments